The Legacies of The Basin of Mexico - Morehart, Christopher T.; Cordova, Carlos E., 1965- (Book collections on Project MUSE., 2023)
"This volume celebrates the contributions from The Basin of Mexico: The Ecological Processes in the Evolution of a Civilization by William T. Sanders, Jeffrey R. Parsons, and Robert S. Santley. This influential work synthesized the results of the Basin of Mexico survey projects, while providing lines of research in Mesoamerica"--